\(\dfrac{3}{2}+\dfrac{2}{3}=\dfrac{9}{6}+\dfrac{4}{6}=\dfrac{13}{6}\)
\(\dfrac{3}{2}+\dfrac{2}{3}=\dfrac{9}{6}+\dfrac{4}{6}=\dfrac{13}{6}\)
Bài 1: (đề 2) Tính
a) \(2\dfrac{3}{8}:3\dfrac{3}{4}x2\dfrac{2}{3}\)=............
b) \(1\dfrac{1}{2}:\dfrac{7}{3}:2\dfrac{5}{6}\)=............
c) \(4\dfrac{2}{3}-1\dfrac{3}{4}:2\dfrac{2}{5}\)=............
Bài 7: Tính
a) \(4\dfrac{2}{5}x8\dfrac{3}{4}-2\dfrac{3}{4}=...............................\)
b) \(2\dfrac{2}{3}+1\dfrac{2}{5}-\dfrac{2}{15}\)=..............................................
c) \(3\dfrac{1}{3}-2\dfrac{2}{3}+1\dfrac{5}{6}=...............................\)
Bài 6: Tìm x, biết
a) \(\dfrac{3}{2}\) x \(\dfrac{4}{5}\) - X =\(\dfrac{2}{3}\)
b) X x 3\(\dfrac{1}{3}\) = 3\(\dfrac{1}{3}\) : 4\(\dfrac{1}{4}\)
c) 5\(\dfrac{2}{3}\) : x = 3\(\dfrac{2}{3}\) - 2\(\dfrac{1}{2}\)
Bài 3 Tìm x
\(\dfrac{1}{2}:3+x=1\dfrac{2}{3}\)
\(2\dfrac{3}{4}-x=\dfrac{5}{6}+\dfrac{2}{3}\)
\(5\dfrac{4}{10}-x\) X\(\dfrac{3}{4}=\dfrac{2}{3}\)
Tìm y
a) 3 \(\dfrac{1}{5}\) : 2\(\dfrac{1}{3}\): y = \(\dfrac{12}{7}\)
b) 3 : y x 3 \(\dfrac{1}{2}\)= \(\dfrac{2}{3}x\dfrac{3}{4}\)
c) \(3\dfrac{2}{3}-y+1\dfrac{3}{4}=2\)
Bài 2 Tìm x
a) 4\(\dfrac{2}{3}:x-\dfrac{3}{5}=\dfrac{4}{3}\)
b) \(\dfrac{4}{3}+2\dfrac{1}{2}\)x \(X=2\)
c) \(X:3\dfrac{1}{3}=2\dfrac{2}{5}+\dfrac{7}{10}\)
Bài 2: (đề 2) Tìm y
a) \(2\dfrac{2}{5}-y:2\dfrac{3}{4}=1\dfrac{1}{2}\) b) \(1\dfrac{1}{4}+2\dfrac{1}{5}\) x \(y=2\dfrac{3}{5}\)
c) \(2\dfrac{4}{5}-2\dfrac{1}{4}:y=\dfrac{3}{4}\) c) \(x:3\dfrac{1}{3}=2\dfrac{2}{5}+\dfrac{7}{10}\)
Tính A= \(\dfrac{1}{2}\)- \(\dfrac{2}{3}\)+\(\dfrac{3}{4}\)-\(\dfrac{4}{5}\)+\(\dfrac{5}{6}\)-\(\dfrac{6}{7}\)-\(\dfrac{6}{5}\)+\(\dfrac{4}{5}\)-\(\dfrac{3}{4}\)+\(\dfrac{2}{3}\)-\(\dfrac{1}{2}\)
Bài 6: ( Đề 1) Tìm y
a) \(3\dfrac{1}{5}:2\dfrac{1}{3}:y=\dfrac{12}{7}\) b) \(3:yx3\dfrac{1}{2}=\dfrac{2}{3}x\dfrac{3}{4}\) c) \(3\dfrac{2}{3}-y+1\dfrac{3}{4}=2\)
tính giá trị biểu thức
\(\dfrac{3}{5}x\dfrac{2}{3}:\dfrac{1}{2}=?\)
\(\dfrac{2}{3}\cdot\dfrac{1}{2}+\dfrac{1}{3}=?\)
\(\left(\dfrac{5}{7}+\dfrac{2}{5}\right):\dfrac{11}{7}=?\)